Risk factors of venous thromboembolism in patients with large ventral hernias - V. A. Klokov; A. N. Khorev; A. A. Baranov (Бюллетень сибирской медицины, 2012)
A study of venous hemodynamics and blood coagulation system in 40 patients operated on for large ventral hernias. Tension free hernia repair under the control of intraabdominal pressure helps to reduce stasis of blood in the veins of the legs. The development of inflammatory complications accompanied by higher levels of markers of coagulation: fibrinogen, C-reactive protein and D-dimer.